Racialized Impacts of Migration Governance in Mali - (:unkn) unknown (My University, 2024)
Perceptions of Africa as a non-racial space are belied by cases such as Mali. This article explores how racial arguments were deployed by black returnees in Bamako after their repatriation from Libya. Race, racialization processes, and racial violence were one of the cornerstones of French colonization in Mali, and then of the post-colonial state. Mali had a complex relationship with its northern neighbour Libya, for many decades a destination for Malian migrants. The fall of the Gaddafi regime in Libya in 2011 created new problems, as both black Malian migrant workers and Tuareg ex-combatants were returned to the country. Both experienced, in different ways, the effects of a migration regime, influenced by European Union programmes. This article shows how racial categories and migration politics intersect in Mali, becoming mutually constituent and interrelated, and leaving various actors, institutions, processes, histories, and multiple scales entangled with each other.
Keywords: African Research